Un element fini mixte tridimensionnel pour le cal cui des contraintes d 'interface - Ate, Alain; Aivazzadeh, Shahram (European Journal of Computational Mechanics, 1999)
In this paper we present an interfacial finite element designed for analysing planar interfaces in a three-dimensional approach. The element is derived from Hellinger-Reissner's mixed variational principle and takes into account the continuity of the displacement and of the transverse stress components through the interface. Stress analysis of a sandwich plate is made to assess the validity and the effectiveness of the element models, with comparisons to closed-form and numerical solutions.